Evolving asymmetric threats in the Balkans - Butiti, Sorin; Mihailovic, Dusan (NATO science for peace and security series. E, Human and societal dynamics, 2011)
The Balkans remains a region characterized by inadequate efficiency of state institutions, social and economic instability, organized crime, corruption and unsatisfactory human and minority rights; any of which could be a source for the re-escalation of violence with an ethnic or religious motivation. This book presents the proceedings of the NATO two-day Advanced Research Workshop (ARW), focused on Evolving Asymmetric Threats in the Balkans, held in Belgrade, Serbia in October 2010. Thirty-eight scientists and representatives from NATO and partner countries attended the workshop, with the aim of enhancing cooperation and strengthening the relationship between participating countries, examining the asymmetric threats still active in the Balkans and assessing their influence upon the security and stability in the region. Following an introductory overview of the characteristics, mutual challenges, risks and threats in the region, the workshop was divided into four sessions which covered: terrorism in the Balkans; religious and ethnic extremism; organized crime and corruption and other threats to the region. Each of the first three sessions was followed by a discussion focusing on a number of issues, including the role of the armed forces, combating organized crime and the smuggling of military equipment. The spirit of cooperation, development, democracy, diplomacy, integration and defense evident throughout the workshop, points the way towards positive collaboration among the member states to improve the situation in this troubled region.